Programa de educación sexual para prevenir el abuso sexual en niños y niñas del quinto año de educación básica de la unidad educativa, Dr. Manuel Cabrera Lozano, periodo 2014-2015 - Rojas Ponce, Karina Alexandra (2016)
Sexual abuse creates a lasting and devastating to child development and family impact; sex education at an early age prevents this type of suffering; for that reason it is the general objective implement a sex education program to prevent sexual abuse in children. descriptive cross-cutting and quasi-experimental design; for the purpose of analytical methods, inductive, deductive, synthetic, historical, logical, understanding, diagnosis, modeling, statistical was used; Tutty Questionnaire was applied in a sample of 23 boys and girls have an average level of knowledge and being victims of sexual abuse; the results of the study found that 65.22% show a medium level of knowledge and skills for self-care sexual abuse (pre-test), after the implementation of the sex education program 100% of children show knowledge and skills to prevent; the program reaches a value of r = 0.74 which means high positive correlation. Conclusion: the knowledge and skills of every child from sexual abuse rose.